2019
DOI: 10.1371/journal.pone.0223847
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities in the rhizosphere, phyllosphere and endosphere of tomato plants

Abstract: Plants harbor diverse bacterial communities, which play crucial roles in plant health and growth, in their rhizosphere, phyllosphere and endosphere. Tomato is an important model for studying plant-microbe interactions, but comparison of its associated bacterial community is still lacking. In this study, using Illumina sequencing of 16S rRNA amplicons, we characterized and compared the bacterial size and community from rootzone soil as well as the rhizosphere, phyllosphere and endosphere of roots, stems, leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
105
2
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(135 citation statements)
references
References 56 publications
18
105
2
10
Order By: Relevance
“…In almost all plant species, the rhizospheric bacterial diversity, in terms of species richness, was much higher than the respective phyllopsheric communities. This is a common finding in similar studies of native and/or cultivated plants in different environments [53][54][55][56][57][58][59][60]. These differences in species richness between the two plant compartments have been attributed to their fundamental physiological and functional differences, as well as the direct impact of their surrounding environments (soil vs air environment).…”
Section: Discussionmentioning
confidence: 63%
“…In almost all plant species, the rhizospheric bacterial diversity, in terms of species richness, was much higher than the respective phyllopsheric communities. This is a common finding in similar studies of native and/or cultivated plants in different environments [53][54][55][56][57][58][59][60]. These differences in species richness between the two plant compartments have been attributed to their fundamental physiological and functional differences, as well as the direct impact of their surrounding environments (soil vs air environment).…”
Section: Discussionmentioning
confidence: 63%
“…Rice endophytic microbiome was observed to consist of diverse genes related to hydrolytic plant-polymer-degrading enzymes, detoxification of reactive oxygen species (ROS), glutathione synthases, and glutathione- S -transferases (GST), autoinducer molecules, and iron acquisition [ 229 ]. Illumina-based 16 rRNA analysis of bacterial community structure of rhizosphere, phyllosphere, and endosphere of tomato plants showed that bacterial richness decreased from root zone soil to rhizosphere to phyllosphere to endosphere, whereas diversity was decreased from root zone soil to rhizosphere to endosphere to phyllosphere [ 230 ]. Proteobacteria was found to be the most abundant phyla associated with tomato plants.…”
Section: Endophytic Pgpr and “Omics” Technologiesmentioning
confidence: 99%
“…plant. Several reports point to a higher richness and microbial diversity in the rhizosphere than the phyllosphere of plants [ 41 , 64 , 65 , 66 ]. This bacterial diversity is correlated with the total community size.…”
Section: Discussionmentioning
confidence: 99%